PERBANDINGAN PENERAPAN SNOWBALL THROWING DAN TEAMS GAMES TOURNAMENT PADA KEMAMPUAN PEMAHAMAN KONSEP DAN PENALARAN MATEMATIKA SISWA - Wiwik Suryaningsih; Nursalam; Suharti (Al asma : Journal of Islamic Education, 2022)
This study discusses the differences in the ability to understand mathematical concepts and reasoning of students who are taught by Snowball Throwing (ST) and Teams Games Tournament (TGT). This study uses a quantitative approach with a quasi-experimental type of research in the form of a non-equivalent control group design. The population in this study were all students of class VIII SMP Negeri 1 Pallangga totaling 350 people with a sample of 32 people each in 2 classes taken. The instrument in this research is a test to measure students’ conceptual understanding and reasoning abilities in the form of pretest and posttest. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis, namely the multivariate mean difference test. The results indicate that there are simultaneous differences in the ability to understand concepts and mathematical reasoning of students who are taught using Snowball Throwing (ST) and Teams Games Tournament (TGT) in class VIII SMPN 1 Pallangga.